Determining the revenue contribution of logistics customer service improvements: A multi criteria decision making approach - Philip Wessely; Erik Hofmann (Decision Analytics, 2014)
In operations and service management generating revenues is as important as reducing costs. Although logistics customer service is an important measure for executives, little research has been conducted to quantify the extent to which improvements of service levels contribute to a company's revenues. The paper applies existing fuzzy-based methods to monetarily determine the revenue contribution of logistics customer service. A logistics customer service-revenue curve and its influencing parameters are derived to obtain a quantitative relation. The method of the analytical hierarchy process is evolved dynamically by involving competitors and customer reactions. A case study from the consumer goods industry illustrates the main findings.
Keywords: 330; Operations management; Fuzzy sets; Analytical hierarchy process; Supply chain initiative; Customer satisfaction; Value creation